PERENCANAAN LAJUR KHUSUS SEPEDA MOTOR PADA RUANG HENTI KHUSUS TERHADAP TINGKAT PELAYANAN SIMPANG BERSINYAL JAMBO TAPE - Muammar Fahmi; Sugiarto Sugiarto; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2020)
Special Stopping Space(RHK) is one of the facilities for motorcycles to stop at intersections during the red phase. RHK functions to separate motorbikes from other vehicles and is expected to reduce the obstacles that come from motorbikes. This Special Stop Room has been tested on a limited scale to support motorbike movement at signaled intersections in major cities in Indonesia. So far RHK at the Jambo Tape intersection has not been optimally functioning because there are still many motorcycle that cannot enter RHK. Therefore, this study aims to determine the level of service on Jambo Tape Intersection. The research was carried out using the simulation method using VISSIM software. The advantage of VISSIM is that it can model simulations in the form of video and get the value of the queue length and the value of time delay just by inputting the data of vehicles passing through the intersection. Traffic volume data is taken on Monday and Wednesday with direct observations in the field. RHK is considered unable to function optimally because there are still many motorbikes that cannot enter RHK. The closure of access (RHK) by four-wheeled vehicles is one of the reasons. Therefore, this study aims to plan the dimensions of motorcycle lanes in Special Stop Space (RHK), and analyze the effect of the level of crossing services using VISSIM software simulation . The advantage of VISSIM is that it can model simulations in the form of video and get the value of the queue length and the value of time delay just by inputting the data of vehicles passing through the intersection. In this study, a survey was conducted to obtain traffic volume, local and geometric velocity. The highest length of the Queue is at arm C, which is on T. Hasan Dek road at 163.36 m. The highest vehicle average delay is 132.119 seconds, the service level category F is greater than 80 seconds. By applying a special route to RHK, the highest volume occurred on Jalan T. Nyak Arief with the existing volume on the T. Nyak Arief road arm at 437 to 520 two-wheeled vehicles / Hour on RHK conditions using motorcycle lanes.